Sir Joseph Barcroft, Cambridge placental and fetal research (1933-1966) and inter-generational Science. - Boyd, R; Boyd, C (2010)
The nature of Cambridge (UK) placental and fetal research in the middle third of the twentieth century is reviewed on the basis of published literature and personal recollection. Joseph Barcroft is a central figure who came to fetal research late in an extremely productive career which is briefly sketched. Contemporaneous Cambridge academics in the field included J.D. Boyd (the authors father), J. Hammond, F.H.A. Marshall, R.A. McCance, J. Needham, A.S. Parkes and Elsie Widdowson. The then current Cambridge academic geography is explained and features of its scientific life such as funding, institutional structure and ethos, teaching and clinical duties, domestic and gender roles, and political context, including war and empire, are briefly considered. The testing of research findings against general principles and use of quantitative thinking are identified as important features. Intergenerational connections, often within individual families, are identified as a striking feature. The long-term impact of Cambridge work of this period; locally, in current trophoblast and feto-placental genetic research, in Oxford in probably influencing G.S. Dawes research leadership, and internationally, especially through D.H. Barron, and through him to the Denver School, is considered. That human placental and embryological specimens collected by J.D. Boyd have received a new lease of life as the "Boyd Collection", including use by Allen Enders is noted. Mechanisms for the maintenance of scientific quality and productivity during the period, mainly through the scientist himself relying on an internalised sense of "obligation", are contrasted with those current in the UK and more widely; formal peer-review at frequent intervals, with subsequent allocation of short-term funding. The strengths and weaknesses of each are considered.